The in Vivo TRPV6 protein starts at a Non-AUG triplet, decoded as methionine, upstream of canonical initiation at AUG * - Fecher-Trost, Claudia; Wissenbach, Ulrich; Beck, Andreas; Schalkowsky, Pascal; Stoerger, Christof; Doerr, Janka; Dembek, Anna; Simon-Thomas, Martin; Weber, Armin; Wollenberg, Peter; Ruppert, Thomas; Middendorff, Ralf; et al. (The journal of biological chemistry, 2013)
TRPV6 channels function as epithelial Ca2+ entry pathways in the epididymis, prostate, and placenta. However, the identity of the endogenous TRPV6 protein relies on predicted gene coding regions and is only known to a certain level of approximation. We show that in vivothe TRPV6 protein has an extended N terminus. Translation initiates at a non-AUG codon, at ACG, which is decoded by methionine and which is upstream of the annotated AUG, which is not used for initiation. The in vitro properties of channels formed by the extended full-length TRPV6 proteins and the so-far annotated and smaller TRPV6 are similar, but the extended N terminus increases trafficking to the plasma membrane and represents an additional scaffold for channel assembly. The increased translation of the smaller TRPV6 cDNA version may overestimate the in vivo situation where translation efficiency may represent an additional mechanism to tightly control the TRPV6-mediated Ca2+ entry to prevent deleterious Ca2+ overload.Background: The TRPV6 amino acid sequence is predicted from its cDNA. Results: The TRPV6 protein purified from human tissues has an extended N terminus not present in the predicted protein. Conclusion: Full-length TRPV6 is trafficked to the plasma membrane, and its translation efficiency tightly controls TRPV6-mediated Ca2+ entry.Significance: This study provides mechanistic insights into the function of the full-length TRPV6.
Gesehen am 04.03.2021